The impact of evidence-based nursing leadership in healthcare settings : a mixed methods systematic review - Välimäki, Maritta; Hu, Shuang; Lantta, Tella; Hipp, Kirsi; Varpula, Jaakko; Chen, Jiarui; Liu, Gaoming; Tang, Yao; Chen, Wenjun; Li, Xianhong (BioMed Central, 2025)
Background: The central component in impactful healthcare decisions is evidence. Understanding how nurse leaders use evidence in their own managerial decision making is still limited. This mixed methods systematic review aimed to examine how evidence is used to solve leadership problems and to describe the measured and perceived effects of evidence-based leadership on nurse leaders and their performance, organizational, and clinical outcomes.
Methods: We included articles using any type of research design. We referred nurses, nurse managers or other nursing staff working in a healthcare context when they attempt to influence the behavior of individuals or a group in an organization using an evidence-based approach. Seven databases were searched until 11 November 2021. JBI Critical Appraisal Checklist for Quasi-experimental studies, JBI Critical Appraisal Checklist for Case Series, Mixed Methods Appraisal Tool were used to evaluate the Risk of bias in quasi-experimental studies, case series, mixed methods studies, respectively. The JBI approach to mixed methods systematic reviews was followed, and a parallel-results convergent approach to synthesis and integration was adopted.
Results: Thirty-one publications were eligible for the analysis: case series (n = 27), mixed methods studies (n = 3) and quasi-experimental studies (n = 1). All studies were included regardless of methodological quality. Leadership problems were related to the implementation of knowledge into practice, the quality of nursing care and the resource availability. Organizational data was used in 27 studies to understand leadership problems, scientific evidence from literature was sought in 26 studies, and stakeholders' views were explored in 24 studies. Perceived and measured effects of evidence-based leadership focused on nurses' performance, organizational outcomes, and clinical outcomes. Economic data were not available.
Conclusions: This is the first systematic review to examine how evidence is used to solve leadership problems and to describe its measured and perceived effects from different sites. Although a variety of perceptions and effects were identified on nurses' performance as well as on organizational and clinical outcomes, available knowledge concerning evidence-based leadership is currently insufficient. Therefore, more high-quality research and clinical trial designs are still needed.
Trail registration: The study was registered (PROSPERO CRD42021259624).